Spectroscopy from Photometry: A Population of Extreme Emission Line Galaxies at 1.7 ≲ z ≲ 6.7 Selected with JWST Medium Band Filters - Withers, Sunna; Muzzin, Adam; Ravindranath, Swara; Sarrouh, Ghassan T. E.; Abraham, Roberto; Asada, Yoshihisa; Bradač, Maruša; Brammer, Gabriel; Desprez, Guillaume; Iyer, Kartheik; Martis, Nicholas; Mowla, Lamiya; et al. (Astrophysical journal. Letters, 2023)
NRC publication: Yes